Small clauses - Cardinaletti, Anna; Guasti, Maria Teresa (Syntax and semantics, 1995)
These previously unpublished articles offer a cross-linguistic perspective on small clauses. They discuss subjects such as the different types of small clauses across languages and lexical items, the internal syntax of small clauses and their structure, and the general topic of the grammar of predication, ranging from a total questioning of the existence of small clauses to claims that they exist in every predication context. The editors' cross-linguistic approach addresses syntactic and lexical issues as well as the relationships between small clauses and language acquisition among children. It surveys the problems raised by small clauses in light of recent developments in the principles and parameter model. The data is drawn from Danish, Dutch, English, Finnish, French, German, Hebrew, Hungarian, Icelandic, Irish, Italian, Norwegian, Portuguese, Russian, Slovak, and Swedish. The contributions share theoretical assumptions about small clauses. The cross-linguistic comparison offers the potential for defining variable and static elements of small clauses, as well as distinguishing ways that they resemble full clauses.